PENATALAKSANAAN FISIOTERAPI PADA KASUS BELL’S PALSY SINISTRA DENGAN MODALITAS INFRAMERAH, ELECTRICAL STIMULATION DAN MIME EXERCISE - Muhammad Fawwaz Malik Azhari; Umi Budi Rahayu; Muhammad Nasuka (Bajang Institute, 2023)
Bell palsy is the most common idiopathic condition of peripheral paralysis of the seventh cranial nerve. Bell palsy causes the inability to move the affected side of the facial muscles fully or partially. About 40,000 new cases of bell palsy are diagnosed each year with a lifetime risk of 1 in 60. Treatment for Bell''s palsy includes electrical stimulation and infrared therapy. The motor points sought were for the movements of closing the mouth, smiling, closing the eyes and frowning. Mime exercise..Mime exercises are performed with a frequency of 2x a week. With 10 repetitions in 5 sets of each movement. Movements included (1) passive eyebrow raising (2) passive winking (3) passive eye opening and closing (4) passive mouth blowing and (5) passive smiling. After the physiotherapy program was carried out for 1 week, it was found that there was no improvement in facial functional ability based on the evaluation results using the ugo fisch scale and the strength of the facial muscles based on the evaluation of MMT values. Patient Mr. D is 27 years old with a diagnosis of bell''s palsy sinistra after being given physiotherapy interventions, such infrared, electrical stimulation, mime therapy as much as 3x in 2 weeks, there are no changes in facial motor functional abilities or facial muscle strength values.